6j-1=3j+6

Simple and best practice solution for 6j-1=3j+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6j-1=3j+6 equation:


Simplifying
6j + -1 = 3j + 6

Reorder the terms:
-1 + 6j = 3j + 6

Reorder the terms:
-1 + 6j = 6 + 3j

Solving
-1 + 6j = 6 + 3j

Solving for variable 'j'.

Move all terms containing j to the left, all other terms to the right.

Add '-3j' to each side of the equation.
-1 + 6j + -3j = 6 + 3j + -3j

Combine like terms: 6j + -3j = 3j
-1 + 3j = 6 + 3j + -3j

Combine like terms: 3j + -3j = 0
-1 + 3j = 6 + 0
-1 + 3j = 6

Add '1' to each side of the equation.
-1 + 1 + 3j = 6 + 1

Combine like terms: -1 + 1 = 0
0 + 3j = 6 + 1
3j = 6 + 1

Combine like terms: 6 + 1 = 7
3j = 7

Divide each side by '3'.
j = 2.333333333

Simplifying
j = 2.333333333

See similar equations:

| -x+16=-7x-8 | | X+(32/X)=0 | | 8(x-1)=4+9x | | 2/5+4=x | | 70-8x=14 | | 5+5x=2x-44 | | X+32/X=0 | | 2/4+5=x | | 4x-16=-4x+24 | | 2y=8y-12 | | 3x-12=-3x+12 | | f+f+3=19 | | x-3x=21 | | 4x-8=-3x+20 | | 4x-4=-2x+44 | | 14=70-8x | | -4-6x=14-10x | | x*x*x-3x=21 | | -3=6-5w+5/2w | | 4x-12=-3x+23 | | x+8=9x-3 | | -2x-9=12x+19 | | n/-3-2=18 | | 12x-5x=42 | | 3x^2-3y^2-5x+8y+8=0 | | 4x+36=-2x | | 1/3d=73 | | 13x-7x=6 | | ln(x^3)+ln(x^2)=32 | | 11x-4x=21 | | 7x^2=-47x+30 | | 4x^2+3y^2-5x+8y-4=0 |

Equations solver categories